The genetic relationship between Alune, Lisabata, Luhu, and Wemale (Western Seram, Indonesia): a historical-comparative linguistics approach - Hendrokumoro; Faradika Darman; Neni Nuraeni; Nadia Khumairo Ma’shumah (Cogent Arts & Humanities)
Language and cultural identity differences can easily lead to a small amount of warfare and confrontation due to a lack of sense of belonging. This study examined the genetic relationship of four languages spoken in Western Seram, consisting of the Alune, Lisabata, Luhu, and Wemale, and its urgency to the relation among four existing tribes by stepping on qualitative and quantitative evidence. To determine language kinship, 200 basic lexical items from Swadesh’s lists were tested on 12 informants. Along with that, 20 additional informants were added for face-to-face interviews to assess historical, philosophical, social, and cultural backgrounds. Despite the inconsistencies in phonological change regularities, the results have revealed that Lisabata and Luhu had the highest percentage of language kinship at 64% with 128 cognates, followed by Lisabata and Alune at 58% with 116 cognates, Luhu and Alune at 57.5% with 114 cognates, Alune and Wemale at 49% with 98 cognates, Wemale and Luhu at 47.5% with 95 cognates, and Wemale and Lisabata at 45% with 90 cognates. Evidence of interconnectedness between the four languages on the family level within the historical frame of Nunusaku mythology can be used further as a milestone to strengthen the relationship between the four ethnic groups.